THE KEPEMIMPINAN VISIONER DALAM PENDIDIKAN ISLAM: MEMBANGUN KARAKTER PESERTA DIDIK MELALUI VISI BERBASIS NILAI - Faroqi, Nisa Amaliyah Rohmah Al; Syukur, Fatah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to explore the role of visionary leadership in Islamic education and its impact on the character development of students at MTs Negeri 6 Kebumen. The method used is a qualitative approach with a case study design, involving semi-structured interviews, participatory observations, and document analysis. The subjects of the research consist of the school principal, teachers, and students who are directly involved in the implementation of visionary leadership. The results indicate that the application of a value-based vision oriented towards Islamic teachings has successfully created a learning environment that supports the character development of students, as evidenced by improvements in discipline, responsibility, and social awareness among the students. The novelty of this research lies in its deeper focus on the integration of value-based vision in Islamic educational leadership, as well as a holistic approach to building student character. This study is expected to contribute to the development of educational leadership theory and its practices, and to serve as a reference for other educational institutions in implementing effective visionary leadership.